IDENTIFIKASI TUJUAN DAN SASARAN PEMBANGUNAN DESA KABUPATEN ACEH BARAT - Nellis Mardhiah (Jurnal Public Policy, 2017)
Research to identify goals and objectives for the development of rural areas implemented by local governments in Aceh Barat by law No. 6 of 2014 concerning Indonesian villages. Government Regulation No. 43 of 2014 on regulations implementing the law on the entire territory of Indonesia. The idea in the construction of the village area, to establish an independent village-based autonomy based on decentralization of policy goals of development planning top-down central government and development activities in bottom-up to the local government at the village level that is able to run continuously to carry out nation-building and livelihood both nations in the economic, political, social, cultural and defence security, and science and technology. The qualitative research method with descriptive approach to the phenomenon of primary and secondary data with the results of previous studies based on linkage with rural development. The theory of this study using the theory of decision-making and the development concept that has been implemented through the analysis of rural development top-down or bottom-up. Identify the goals and objectives of rural development is to create an autonomous rural development in a sustainable community economic empowerment. Keywords: Identification, Goals, Objectives, Development, Village